Sex-Positive Spirituality: Integrating Spirituality and Sexuality Into Therapy - Browning, Sue; Smith, Stewart J. (Canadian Journal of Counselling and Psychotherapy, 2025)
In this paper, the authors explore the challenges and the opportunities for therapists to help their clients bridge the divide between their religious and spiritual beliefs and their sexual practices and identities. The therapeutic work experiences of both authors are primarily with clients who identify with some expression of the Christian faith, hence the focus of this article. The article emphasizes the importance of therapists collaborating holistically with clients who identify as spiritual/religious, and while therapists having prior knowledge of spirituality/religion is helpful, it is not necessary. The article concludes that, in order to work effectively with clients who identify as spiritual or religious, therapists must include spirituality/religion in the healing process.